COMPARATIVE ANALYSIS OF CHANGES IN THE FLUCTUATING ASYMMETRY OF THE HANGING BIRCH AND SMALL-LEAVED LINDEN LEAVES IN THE GRADIENT OF ROAD TRANSPORT AIR POLLUTION (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The fluctuating asymmetry (FA) of a plant leaf is used for bioindication and environmental monitoring. However, the specific features of FA responses of various leaf traits to air pollution have not been studied sufficiently. Analysis of this issue using the example of Betula pendula and Tilia cordata leaf with roadside air pollution has shown that FA did not change in the polluted areas in the species, which is more resistant to pollution (T. cordata). However, in the species, which is more sensitive to pollution (B. pendula), there was an increase in the FA of three out of five leaf measurements in the pollution gradient, while the integral FA indicator did not change. Thus, when using the FA of a plant leaf in monitoring, it is necessary to take into account the species resistance of plants to pollutants and the different sensitivity of the leaf FA traits to air pollution.
Keywords: fluctuating asymmetry; motor transport; developmental stability; developmental noise; pollutants; leaf measurements